Lithium manganese iron phosphate material as well as preparation method and application thereof

Through the double-layer coating technology, the coordinated cooperation between carbon materials and carbon nitride and conductive polymers is used to solve the problem of low conductivity of lithium manganese iron phosphate positive electrode materials, which significantly improves its electrochemical performance and the overall performance of lithium-ion batteries. .

CN119208567AActive Publication Date: 2024-12-27福建龙净储能电池有限公司

Patent Information

Application Number
CN202411357101.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The conductivity of lithium manganese iron phosphate cathode material is low, resulting in poor rate performance, uneven carbon coating and low ionic conductivity, which affects the electrochemical performance of lithium-ion batteries.

Method used

Using double-layer cladding technology, the first cladding layer consists of carbon material, the second cladding layer consists of carbon nitride and conductive polymers (such as polypyrrole), which cooperates to improve the conductivity and is subject to hydrothermal method and spraying. The pyrolysis method achieves uniform coating and doping.

Benefits of technology

The conductivity, cycle stability and rate performance of lithium manganese iron phosphate material has been significantly improved, and the overall performance of the battery has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063922690000141
    Figure BDA0005063922690000141
  • Figure BDA0005063922690000151
    Figure BDA0005063922690000151
Patent Text Reader

Abstract

The invention provides a lithium manganese iron phosphate material as well as a preparation method and application thereof. The lithium manganese iron phosphate material sequentially comprises a lithium manganese iron phosphate matrix inner core, a first coating layer and a second coating layer from inside to outside, the first coating layer comprises a carbon material, the second coating layer comprises a composite material, and the composite material comprises carbon nitride and a conductive polymer. Through doping and coating of the carbon material in the first coating layer and synergistic cooperation of the conductive polymer and the carbon nitride in the second coating layer, the conductivity of the lithium manganese iron phosphate material is improved, and the cycling stability, the capacity and the rate capability of the lithium manganese iron phosphate material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium manganese iron phosphate material and a preparation method and application thereof. Background Art

[0002] There are many types of positive electrode materials for lithium-ion batteries. Lithium manganese iron phosphate (LMFP) positive electrode material is comparable to lithium iron phosphate because of its safety performance. In particular, it can solve many safety problems under low temperature conditions. In terms of capacity and energy density, it is close to ternary 523 materials, 10-20% higher than lithium iron phosphate positive electrode materials. At the same time, the cost is only 5-6% higher than lithium iron phosphate. It has many advantages such as high working voltage and excellent cycle performance, and is easier to be used in combination with high-energy ternary materials. It has become a current research hotspot. However, due to the one-dimensional conduction of lithium ions in olivine-type positive electrode materials, its ion conductivity is low. Therefore, in terms of electron transmission capacity, the conductivity of lithium manganese iron phosphate is lower than that of lithium iron phosphate with semiconductor properties. The conductivity of lithium iron phosphate (LMFP) is 10 -9 S / cm, while lithium manganese iron phosphate is only 10 -13 S / cm. Therefore, improving the conductivity of lithium manganese iron phosphate and improving its rate performance are essential to improving battery performance.

[0003] At present, the technical solutions for improving the conductivity of LMFP focus on carbon coating and ion doping. Carbon coating mainly improves electronic conductivity, while ion doping mainly improves ion diffusion coefficient and conductivity.

[0004] CN105047922A discloses a carbon-coated lithium manganese iron phosphate positive electrode material and a preparation method. The chemical formula of carbon-coated lithium manganese iron phosphate is C-Li 1-x M x Mn y Fe 1-y PO4, where C represents the compound Li 1-x M x Mn y Fe 1-y PO4 cross-linked carbon, wherein x and y are numbers, and 0<x≤0.1, 0.4≤y<1, and M is selected from transition metals or mixtures of transition metals in the first row of the periodic table. The preparation method comprises: firstly synthesizing ferromanganese oxalate, then ball-milling it with a carbon source, a lithium salt and a phosphorus source to a certain particle size, and then sintering in a protective atmosphere to obtain a target product.

[0005] CN115332516A provides a magnesium and nickel co-doped lithium iron manganese phosphate positive electrode material and a preparation method thereof, comprising a positive electrode active material and a coating material composited on the surface of the positive electrode active material, wherein the positive electrode active material comprises a lithium iron manganese phosphate matrix and magnesium and nickel co-doped in the lithium iron manganese phosphate matrix, wherein the magnesium doping weight percentage is 0.5-3%, and the nickel doping weight percentage is 0.5-3%. The preparation method comprises the following steps: S1, dissolving a lithium source, a phosphorus source, an iron source, a manganese source, a magnesium source, and a nickel source in a solvent and continuously stirring, and dropping a carbon source until the mixture is stirred into a gel state; S2, drying the gel state mixture to obtain a dry gel; S3, placing the dry gel in a protective atmosphere for calcination to obtain a carbon-coated magnesium and nickel co-doped lithium iron manganese phosphate positive electrode material.

[0006] Although the above-mentioned literature has respectively carried out carbon coating and doping treatment on lithium manganese iron phosphate positive electrode materials, LMFP still has the problems of uneven carbon coating and low ion conductivity. The carbon material of the coating layer is still prone to defects during the preparation process. These defects will aggravate the side reactions of the electrolyte on the surface of the lithium manganese iron phosphate material as active sites in lithium-ion batteries, resulting in an increase in the impedance of the battery in the later stage. In addition, the incompletely coated LMFP material has poor reversibility during the charge and discharge process and is prone to polarization, resulting in low capacity. The low ion conductivity will also result in poor rate performance of the material.

[0007] Therefore, how to improve the conductivity of lithium manganese iron phosphate positive electrode materials and further improve their electrochemical performance is currently in urgent need of research. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lithium iron manganese phosphate material and a preparation method and application thereof. The present invention improves the conductivity of the lithium iron manganese phosphate material through double-layer coating of carbon material and composite material, and improves the cycle stability, capacity and rate performance of the lithium iron manganese phosphate material.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a lithium iron manganese phosphate material, which includes, from the inside to the outside, a lithium iron manganese phosphate matrix core, a first coating layer and a second coating layer; the first coating layer includes a carbon material, and the second coating layer includes a composite material, and the composite material includes carbon nitride and a conductive polymer.

[0011] The lithium iron manganese phosphate material provided by the present invention improves the internal conductivity of the lithium iron manganese phosphate material through the doping coating of the carbon material in the first coating layer, and the lithium iron manganese phosphate material coated once is subjected to a secondary coating, and the secondary coated conductive polymer and carbon nitride further improve the conductivity, wherein the carbon nitride has a graphite-like structure, and the stacking distance between its aromatic layers is relatively low (0.319nm), which can show a stronger bond and provide more charge transfer perpendicular to the plane than graphite. The incorporation of nitrogen and the carbon matrix can improve the conductivity of the material, thereby realizing effective charge transfer. In addition, the conductive polymer can also adsorb manganese ions precipitated due to the Jan-Taylor effect, reduce the structural instability of the lithium iron manganese phosphate material caused by the precipitation of manganese ions, and jointly improve the cycle stability, capacity and rate performance of the lithium iron manganese phosphate material.

[0012] In the present invention, the first coating layer and the second coating layer cooperate with each other to achieve the simultaneous improvement of conductivity, cycle performance, capacity and rate performance; and the coating order between the first coating layer and the second coating layer cannot be changed. Once changed, the composite material of the second coating layer will not be able to effectively adsorb the manganese ions precipitated due to the Jan-Taylor effect, and the stability of the LMFP structure cannot be maintained.

[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] Preferably, the D50 of the lithium manganese iron phosphate matrix core is 650-1050nm, for example, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm or 1050nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the thickness of the first coating layer and the thickness of the second coating layer are independently 30 to 50 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the carbon material comprises a pyrolytic carbon material.

[0017] Preferably, the core of the lithium manganese iron phosphate matrix is ​​also doped with carbon material.

[0018] The present invention dopes and coats the carbon material in the inner core of the lithium iron manganese phosphate matrix, that is, performs internal doping and realizes external coating, realizes close contact between the first coating layer and the inner core, and improves the internal conductivity of the inner core.

[0019] Preferably, the conductive polymer comprises polypyrrole.

[0020] In the present invention, the conductive polymer is polypyrrole, which can better absorb the manganese ions precipitated due to the Jan-Taylor effect and reduce the structural instability of the lithium manganese iron phosphate material caused by the precipitation of manganese ions.

[0021] In the present invention, by combining carbon nitride and polypyrrole, a good composite of the two can be achieved without affecting the normal performance of the composite material on the lithium iron manganese phosphate matrix core, and the electrochemical properties of the final lithium iron manganese phosphate material are better improved.

[0022] Preferably, the conductive polymer is in-situ grown on the surface of the carbon nitride.

[0023] In the present invention, in the composite material, the conductive polymer is in-situ grown on the surface of the carbon nitride, which can adsorb the manganese ions precipitated due to the Jan-Taylor effect, thereby reducing the structural instability of the LMFP caused by the precipitation of manganese ions.

[0024] In a second aspect, the present invention provides a method for preparing the lithium iron manganese phosphate material as described in the first aspect, the preparation method comprising the following steps:

[0025] The lithium manganese iron phosphate precursor material and the carbon source are coated and mixed, and carbonized to obtain an intermediate material;

[0026] The intermediate material and the composite material are coated to obtain the lithium manganese iron phosphate material;

[0027] Wherein, the composite material comprises carbon nitride and a conductive polymer.

[0028] The preparation method provided by the present invention realizes uniform coating of carbon materials and composite materials on the surface of lithium iron manganese phosphate matrix materials, and also realizes uniform doping of carbon materials in the core; the prepared lithium iron manganese phosphate material has high electrical conductivity and excellent cycle performance, capacity and rate performance.

[0029] Preferably, the lithium manganese iron phosphate precursor material is prepared by a hydrothermal method;

[0030] Preferably, the hydrothermal method for preparing lithium iron manganese phosphate comprises: mixing a lithium source, a phosphorus source, an iron source and a manganese source, and performing a hydrothermal reaction to obtain the lithium iron manganese phosphate precursor material.

[0031] It should be noted that the specific material type selection and preparation parameter regulation of the lithium manganese iron phosphate precursor material prepared by the hydrothermal method in the present invention are conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments according to actual needs;

[0032] Exemplarily, the present invention provides a specific method for preparing a lithium manganese iron phosphate precursor material:

[0033] Lithium source, phosphorus source, iron source and manganese source are based on the chemical formula LiMn x Fe 1-x PO4 (0.5<x≤0.8, preferably x=0.6) ratio to mix the raw materials, after mixing, obtain the reaction solution to be reacted, and subject the reaction solution to a hydrothermal reaction at 180~240℃ for 5~20h. After the hydrothermal reaction is completed, the lithium manganese iron phosphate precursor material is obtained;

[0034] Optionally, the lithium source includes but is not limited to one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium chloride, lithium phosphate and lithium acetate; the phosphorus source includes but is not limited to one or more of phosphoric acid, diammonium phosphate, ammonium phosphate, pyrophosphoric acid, metaphosphoric acid and phosphorus pentoxide; the iron source includes but is not limited to one or more of ferrous oxalate, ferrous sulfate, ferrous nitrate, ferrous phosphate and ferrous carbonate; the manganese source includes but is not limited to one or more of manganese acetate, manganese nitrate, manganese sulfate, manganese carbonate and manganese chloride;

[0035] Optionally, the temperature of the hydrothermal reaction can be 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, etc., and the time of the hydrothermal reaction can be 5h, 8h, 10h, 13h, 15h, 18h or 20h, etc.

[0036] Preferably, the mass ratio of the precursor to the carbon source is 1:(0.05-0.3), for example 1:0.05, 1:0.1, 1:0.13, 1:0.15, 1:0.18, 1:0.2, 1:0.25 or 1:0.3, etc., preferably 1:(0.1-0.2), but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In the present invention, the mass ratio of the precursor to the carbon source is 1:(0.05-0.3), which can achieve uniform coating of the carbon material after carbonization without affecting the gram capacity of the lithium iron manganese phosphate material, and is more conducive to improving the electrical conductivity of the material; further, the type of carbon source is also selected by conventional technology, and the material types of carbon sources that can be pyrolyzed and carbonized are all applicable to the present invention, including but not limited to at least one of phenolic resin, carbon gel or citric acid.

[0038] Preferably, the coated mixed material is subjected to spray pyrolysis carbonization to obtain the intermediate material.

[0039] In the present invention, carbonization is performed by spray pyrolysis to ensure uniform distribution of carbon material in the first coating layer. The carbon material can further be doped into the inner core of the lithium manganese iron phosphate matrix and uniformly distributed inside, thereby improving the internal conductivity.

[0040] Preferably, the composite material is obtained by in-situ growth of a conductive polymer on a carbon nitride surface.

[0041] In the present invention, there is no special limitation on the polymerization method of the conductive polymer and the preparation method of carbon nitride (carbon nitride can also be directly purchased), and the present invention is applicable to conventional technical methods for preparing the above substances.

[0042] Exemplarily, the present invention provides a method for preparing carbon nitride, the preparation method comprising the following steps:

[0043] Melamine was placed in a closed porcelain boat and heated to 500°C for 4 h at a heating rate of 3°C / min in an air atmosphere. The obtained sample was washed three times with deionized water at a speed of 10000 rpm for 10 min to remove any other residues, and then dried in an oven at 90°C for 24 h. Finally, it was fully cooled to room temperature and fully ground with a mortar to obtain carbon nitride (g-C3N4);

[0044] The present invention also provides a specific method for preparing a composite material in which a conductive polymer is in-situ grown on a carbon nitride surface, the preparation method comprising the following steps:

[0045] The conductive polymer monomer and the initiator are added to deionized water and stirred continuously for about 8 to 10 hours to obtain a uniform solution. Under ultrasonic conditions, carbon nitride is added to the above solution and ultrasonicated. Under the action of the initiator, the monomer can generate a conductive polymer in situ on the surface of the carbon nitride (g-C3N4), and a composite material is obtained after drying.

[0046] Optionally, the initiator includes ammonium persulfate, and the amount of the initiator added is adaptively regulated according to the amount of the monomer added;

[0047] Optionally, the conductive polymer monomer includes at least one of an aniline monomer, a thiophene monomer, a pyrrole monomer, a furan monomer, a thiazole monomer or a pyridine monomer;

[0048] Optionally, the drying method comprises freeze drying.

[0049] Preferably, during the in-situ growth process, the solute mass ratio of the conductive polymer monomer to carbon nitride in the solution is 1:(100-120), for example 1:105, 1:110, 1:115, or 1:120, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the mass ratio of the intermediate material to the composite material is 1:(1-3), for example 1:1, 1:1.3, 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.5, 1:2.8 or 1:3, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In the present invention, the mass ratio of the intermediate material to the composite material is 1:(1-3), which can better achieve uniform coating of the composite material in the second coating layer and better exert the synergistic effect of the conductive polymer and carbon nitride.

[0052] Preferably, the coating treatment includes mixing the intermediate material with the composite material and then heat treating the mixture, and the heat treatment temperature is 150-250°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] Preferably, the coated product is subjected to spray granulation to obtain the lithium manganese iron phosphate material.

[0054] In the present invention, the heat treatment during the coating process and the subsequent spray granulation both achieve better uniform coating of the second coating layer. After the heat treatment, the intermediate material and the composite material are mixed more uniformly.

[0055] As a preferred technical solution, the preparation method comprises the following steps:

[0056] The lithium source, phosphorus source, iron source and manganese source are mixed and subjected to hydrothermal reaction to obtain a lithium iron manganese phosphate precursor;

[0057] The lithium manganese iron phosphate precursor material and the carbon source are coated and mixed at a ratio of 1: (0.05-0.3), and spray pyrolysis and carbonization are performed to obtain an intermediate material;

[0058] The intermediate material and the composite material are mixed in a mass ratio of 1:(1-3), heat treated at 150-250° C., and spray granulated to obtain the lithium manganese iron phosphate material;

[0059] The composite material comprises carbon nitride and a conductive polymer, and the conductive polymer is in-situ grown on the surface of the carbon nitride.

[0060] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium iron manganese phosphate material as described in the first aspect or the lithium iron manganese phosphate prepared by the preparation method as described in the second aspect.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] The lithium iron manganese phosphate material provided by the present invention improves the internal conductivity of the lithium iron manganese phosphate material by doping and coating the carbon material in the first coating layer, and the lithium iron manganese phosphate material coated once is subjected to a secondary coating, and the secondary coated conductive polymer and carbon nitride further improve the conductivity, wherein the carbon nitride has a graphite-like structure, and the stacking distance between its aromatic layers is relatively low (0.319nm), which can show a stronger bond and provide more charge transfer perpendicular to the plane than graphite. The incorporation of nitrogen and the carbon matrix can improve the conductivity of the material, thereby realizing effective charge transfer. In addition, the conductive polymer polypyrrole can also adsorb manganese ions precipitated due to the Jan-Taylor effect, and reduce the structural instability of the lithium iron manganese phosphate material caused by the precipitation of manganese ions. The two together improve the cycle stability, capacity and rate performance of the lithium iron manganese phosphate material. DETAILED DESCRIPTION

[0063] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0064] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0065] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0066] Example 1

[0067] The present embodiment provides a lithium iron manganese phosphate material, which includes, from the inside to the outside, a lithium iron manganese phosphate matrix core (chemical formula LiMn 0.6 Fe 0.4 PO4, D50 is 850nm), a first coating layer and a second coating layer (the thickness range of the first coating layer and the second coating layer is 30-50nm); the first coating layer includes a pyrolytic carbon material, and the second coating layer includes a composite material, the composite material includes carbon nitride and polypyrrole (PPy), and the polypyrrole is in-situ grown on the surface of the carbon nitride.

[0068] The preparation method of the lithium manganese iron phosphate is as follows:

[0069] S1:

[0070] A lithium iron manganese phosphate precursor material was prepared: at room temperature, 0.92 mol of lithium carbonate (Li2CO3) and 0.34 mol of phosphoric acid (H3PO4) were added to 300 mL of deionized water and stirred for 20 min on a magnetic stirrer to obtain a lithium phosphate solution, 0.26 mol of manganese carbonate (MnCO3) and 0.1 mol of iron phosphate (FePO4) were added to 100 mL of deionized water and stirred for 20 min on a magnetic stirrer to obtain a metal salt solution, and finally the lithium phosphate solution and the metal salt solution were mixed and the pH was adjusted to 6.5 with a sodium hydroxide solution, and then transferred to a high-pressure reactor and reacted at 180° C. for 8 h to obtain a solution A (lithium iron manganese phosphate precursor material);

[0071] The lithium iron manganese phosphate precursor material product in solution A and the citric acid solution were mixed at a mass ratio of 1:0.15 and atomized using a 1.7 MHz ultrasonic sprayer. The atomized aerosol was then introduced into a vertical quartz device heated to 400°C with an air flow rate of 10 L / min. Finally, the obtained powder was treated at 500°C in an air atmosphere for 1 h to obtain lithium iron manganese phosphate coated with a pyrolytic carbon source. 0.6 Fe 0.4 PO4 / C (intermediate material with the first coating layer coated on the surface of the lithium manganese iron phosphate matrix core);

[0072] S2:

[0073] Preparation of carbon nitride: Melamine was placed in a closed porcelain boat and heated at 500°C for 4 h at a heating rate of 3°C / min in an air atmosphere. The obtained sample was washed three times with deionized water at a speed of 10000 rpm for 10 min to remove any other residues, and then dried in an oven at 90°C for 24 h. Finally, it was fully cooled to room temperature and fully ground with a mortar to obtain carbon nitride (g-C3N4);

[0074] Preparation of composite materials: pyrrole monomer and ammonium persulfate in the solution are added to 1000 ml of deionized water at a solute mass ratio of 1:746, and the mixture is continuously stirred at 500 rpm for about 8 hours to obtain a uniform solution. Under ultrasonic conditions of 45 Hz, carbon nitride is added to the above solution at a solute mass ratio of 1:112 to achieve uniform dispersion of the carbon nitride-polypyrrole (PPy) composite material (g-C3N4 / PPy) composite solution. The pyrrole monomer can generate polypyrrole on the surface of carbon nitride (g-C3N4) under the action of ammonium persulfate initiator; the obtained product is centrifuged at 10000 rpm for 10 minutes and washed three times with deionized water to remove any other residues, and the composite material of carbon nitride and polypyrrole (g-C3N4 / PPy) is obtained after freeze drying for 12 hours;

[0075] There is no order of precedence between steps S1 and S2;

[0076] S3: The intermediate material obtained in S1 and the composite material (g-C3N4 / PPy) obtained in S2 are ball-milled at a mass ratio of 1:2 for 2 hours, and then kept at 180°C for 15 hours (heat treatment) to obtain a molten blend; finally, the molten blend is dried and granulated by spray drying, and finally fully ground in a mortar to obtain the lithium manganese iron phosphate material LiMn 0.6 Fe 0.4 PO4 / C@g-C3N4 / PPy.

[0077] Example 2

[0078] The difference between this embodiment and embodiment 1 is that the pyrolysis carbon source in step S1 of this embodiment is carbon gel.

[0079] The rest of the preparation methods and parameters were the same as those in Example 1.

[0080] Example 3

[0081] The difference between this embodiment and embodiment 1 is that the pyrolysis carbon source in embodiment S1 is phenolic resin.

[0082] The rest of the preparation methods and parameters were the same as those in Example 1.

[0083] Example 4

[0084] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the mass ratio of the intermediate material obtained in S1 to the composite material obtained in S2 is 1:1.

[0085] The rest of the preparation methods and parameters were the same as those in Example 1.

[0086] Example 5

[0087] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the mass ratio of the intermediate material obtained in S1 to the composite material obtained in S2 is 1:1.5.

[0088] The rest of the preparation methods and parameters were the same as those in Example 1.

[0089] Example 6

[0090] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the mass ratio of the intermediate material obtained in S1 to the composite material obtained in S2 is 1:2.5.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] Example 7

[0093] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the mass ratio of the intermediate material obtained in S1 to the composite material obtained in S2 is 1:3.

[0094] The rest of the preparation methods and parameters were the same as those in Example 1.

[0095] Example 8

[0096] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the mass ratio of the intermediate material obtained in S1 to the composite material obtained in S2 is 1:0.5.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Example 9

[0099] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the mass ratio of the intermediate material obtained in S1 to the composite material obtained in S2 is 1:4.

[0100] The rest of the preparation methods and parameters were the same as those in Example 1.

[0101] Comparative Example 1

[0102] The difference between this comparative example and Example 1 is that the lithium manganese iron phosphate material provided in this comparative example does not contain a second coating layer;

[0103] In the preparation method, steps S2 and S3 are not performed, and only step S1 is performed.

[0104] The rest of the preparation methods and parameters were the same as those in Example 1.

[0105] Comparative Example 2

[0106] The difference between this comparative example and Example 1 is that the lithium manganese iron phosphate material provided in this comparative example does not contain the first coating layer;

[0107] In the preparation method, after obtaining the lithium iron manganese phosphate precursor material, the lithium iron manganese phosphate precursor material is directly used as an intermediate material to carry out the preparation processes of steps S2 and S3; and the carbon coating process in step S1 is not carried out.

[0108] The rest of the preparation methods and parameters were the same as those in Example 1.

[0109] Comparative Example 3

[0110] The difference between this comparative example and Example 1 is that in the lithium manganese iron phosphate material provided in this comparative example, the second coating layer does not contain carbon nitride, that is, the second coating layer is polypyrrole.

[0111] In the preparation method, the preparation process of carbon nitride is not carried out, and the polymerization of polypyrrole is directly carried out.

[0112] The rest of the preparation methods and parameters were the same as those in Example 1.

[0113] The powder resistivity of the lithium iron manganese phosphate materials provided in Examples 1-9 and Comparative Examples 1-3 was tested: At 25°C, the lithium iron manganese phosphate materials prepared in Examples 1-9 and Comparative Examples 1-3 were tested using a four-probe powder resistivity meter, and the resistivity value was recorded when the pressure reached 20 MPa. The test results are shown in Table 1.

[0114] Table 1

[0115] Resistivity (Ω·cm) Example 1 22.34 Example 2 24.53 Example 3 24.12 Example 4 26.78 Example 5 25.89 Example 6 24.87 Example 7 25.93 Example 8 27.88 Example 9 26.03 Comparative Example 1 30.74 Comparative Example 2 33.67 Comparative Example 3 30.23

[0116] The lithium manganese iron phosphate materials provided in Examples 1-9 and Comparative Examples 1-3 were used as positive electrode materials to prepare batteries and perform tests:

[0117] 1. Preparation of button cells

[0118] The lithium iron manganese phosphate material obtained in Example 1-9 and Comparative Example 1-3: PVDF glue: carbon black (SP): CNT were weighed at a mass ratio of 95:2:0.8:0.6, and the total weight was 10g. The weighed materials were poured into a ball mill, stirred for 10 minutes using a high-speed swing ball mill, and a uniformly stirred slurry was obtained. Then, the slurry was evenly coated on the current collector aluminum foil, dried at 105°C for 4 hours in a vacuum drying oven, rolled to a compaction density of 2.35mg / cm3, and then die-cut, weighed, and dried at 105°C for 2 hours in a vacuum drying oven. Then, the half-cell was assembled in a glove box. With metallic lithium as the negative electrode, the assembly process of the button battery was completed in a glove box filled with argon gas according to the placement order of the negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm, electrolyte, positive electrode (electrode sheet) positive electrode shell, and finally the battery was packaged with a battery sealing machine.

[0119] 2. Performance Testing

[0120] (1) Charge and discharge capacity

[0121] At 25°C, after the lithium-ion battery has been left to stand for 12 hours, it is charged at a constant current rate of 1C to a voltage of 4.2V, left to stand for 5 minutes, and then discharged at a rate of 1C to 2.5V, left to stand for 5 minutes, and the first cycle charge and discharge capacity is recorded;

[0122] (2) Cycle performance

[0123] At 25°C, the lithium-ion battery is charged at a constant current rate of 1C to a voltage of 4.2V, left to stand for 5 minutes, and then discharged at a rate of 1C to 2.5V, left to stand for 5 minutes. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 200 times at 25°C under the above conditions and the charge and discharge capacity is recorded and the capacity retention rate is calculated;

[0124] The above test results are shown in Table 2.

[0125] Table 2

[0126]

[0127]

[0128] From Table 1 and Table 2, we can get:

[0129] It can be seen from the data results of Examples 1-8 that the lithium manganese iron phosphate material provided by the present invention has excellent electrical conductivity, capacity, cycle performance and rate performance.

[0130] From the data results of Examples 1 and 4-9, it can be seen that the mass ratio of the intermediate material to the composite material is too small, and a suitable ratio should be selected for coating. Too high or too low will affect the gram capacity of the active substance and the cycle retention rate at 1C rate.

[0131] From the data results of Example 1 and Comparative Examples 1-3, it can be seen that the discharge capacity and capacity retention rate of the lithium manganese iron phosphate positive electrode material provided by the present invention are far less than those of Example 1 with two layers of carbon coating, indicating that the first coating layer and the second coating layer synergistically improve the conductivity inside and outside, improve the cycle stability and increase the capacity of the battery, wherein the capacity retention rate of Comparative Examples 2 and Comparative Examples 3 is higher than that of Comparative Example 1, which should be because the polypyrrole in the carbon nitride and polypyrrole composite material (g-C3N4 / PPy) can adsorb the manganese ions precipitated due to the Jan-Taylor effect, reduce the structural instability of LMFP caused by the precipitation of manganese ions, and thus improve the cycle performance. In addition, the resistivity of Comparative Example 3 is lower than that of Comparative Example 2, indicating that the main factor that improves the conductivity is the coating and doping of the pyrolytic carbon source, and the addition of carbon nitride can further improve the conductivity and improve the battery performance.

[0132] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium manganese iron phosphate material, characterized in that: The lithium manganese iron phosphate material includes a lithium manganese iron phosphate matrix core, a first coating layer and a second coating layer from the inside to the outside; the first coating layer includes a carbon material, and the second coating layer includes a composite material, and the composite material includes carbon nitride and a conductive polymer.

2. The lithium iron manganese phosphate material according to claim 1, characterized in that: The D50 of the lithium manganese iron phosphate matrix core is 650-1050nm.

3. The lithium iron manganese phosphate material according to claim 1, characterized in that: The thickness of the first coating layer and the thickness of the second coating layer are each independently 30 to 50 nm; Preferably, the carbon material comprises a pyrolyzed carbon material; Preferably, the core of the lithium manganese iron phosphate matrix is ​​also doped with carbon material.

4. The lithium iron manganese phosphate material according to claim 1 or 3, characterized in that: The conductive polymer includes polypyrrole; Preferably, the conductive polymer is in-situ grown on the surface of the carbon nitride.

5. A method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The lithium manganese iron phosphate precursor material and the carbon source are coated and mixed, and carbonized to obtain an intermediate material; The intermediate material and the composite material are coated to obtain the lithium manganese iron phosphate material; Wherein, the composite material comprises carbon nitride and a conductive polymer.

6. The preparation method according to claim 5, characterized in that: The lithium manganese iron phosphate precursor material is prepared by a hydrothermal method; Preferably, the hydrothermal method for preparing lithium iron manganese phosphate comprises: mixing a lithium source, a phosphorus source, an iron source and a manganese source, and performing a hydrothermal reaction to obtain the lithium iron manganese phosphate precursor material.

7. The preparation method according to claim 5 or 6, characterized in that: The mass ratio of the precursor to the carbon source is 1:(0.05-0.3), preferably 1:(0.1-0.2); Preferably, the coated mixed material is subjected to spray pyrolysis carbonization to obtain the intermediate material.

8. The preparation method according to claim 5, characterized in that: The composite material is obtained by in-situ growth of a conductive polymer on the surface of carbon nitride; Preferably, during the in-situ growth process, the solute mass ratio of the conductive polymer monomer to the carbon nitride in the solution is 1:(100-120); Preferably, the mass ratio of the intermediate material to the composite material is 1:(1-3); Preferably, the coating treatment comprises mixing the intermediate material with the composite material and then heat treating the mixture, and the heat treatment temperature is 150-250°C; Preferably, the coated product is subjected to spray granulation to obtain the lithium manganese iron phosphate material.

9. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: The lithium source, phosphorus source, iron source and manganese source are mixed and subjected to hydrothermal reaction to obtain a lithium iron manganese phosphate precursor; The lithium manganese iron phosphate precursor material and the carbon source are coated and mixed at a ratio of 1: (0.05-0.3), and spray pyrolysis and carbonization are performed to obtain an intermediate material; The intermediate material and the composite material are mixed in a mass ratio of 1:(1-3), heat treated at 150-250° C., and spray granulated to obtain the lithium manganese iron phosphate material; The composite material comprises carbon nitride and a conductive polymer, and the conductive polymer is in-situ grown on the surface of the carbon nitride.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron manganese phosphate material as described in any one of claims 1 to 4 or the lithium iron manganese phosphate prepared by the preparation method as described in any one of claims 5 to 9.

Citation Information

Patent Citations

  • Mononuclear multi-shell lithium iron manganese phosphate positive electrode material, preparation method and secondary battery

    CN114843507A

  • Positive electrode lithium supplementing material and preparation method and application thereof

    CN116544365A

  • Lithium supplement additive, positive pole piece, battery and electric device

    CN117239104A

  • Lithium battery positive electrode material and preparation method thereof, positive electrode plate and lithium battery

    CN117936743A

  • Current collector, electrode sheet, secondary battery, and electronic device

    WO2024179358A1

Cited By

  • Lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN119943917A

  • Lithium iron manganese phosphate positive electrode material and preparation method thereof

    CN119943917B

  • High-compaction lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN120039852A

  • Chitosan-based nitrogen-doped carbon-coated lithium iron phosphate material and preparation method thereof

    CN122417858A